The Influence of Specimen Geometry and Strain Rate on the Portevin-Le Chatelier Effect and Fracture in an Austenitic FeMnC TWIP Steel - Jidong Kang; Liting Shi; Jie Liang; Babak Shalchi-Amirkhiz; Colin Scott (Metals, 2020)
We studied the Portevin-Le Chatelier effect and fracture behavior of a FeMnC TWIP steel using high speed digital image correlation by varying the specimen geometry (flat vs. round) and test strain rate (0.001 vs. 0.1 s−1). The results show that the mean flow stress, the mean strain hardening rate and the mean strain rate sensitivity parameters are all independent of the specimen geometry and are uncorrelated with the presence or not of Portevin-Le Chatelier (PLC) bands, the type of PLC bands observed or the critical strain for band formation. However, both the fracture strains and stresses and the PLC behavior are highly geometry and/or strain rate dependent. Dynamic strain aging (DSA) and in particular the presence of PLC instabilities appears to play an important but as yet unclear role in promoting premature necking and final fracture.